PRAGMATIC FEATURES OF THE TEXT (Ustozlar uchun, 2025)
Abstract The article explores the pragmatic features of the text as an essential aspect of its communicative organization and functional realization. Pragmatics, as a branch of linguistics, studies the relationship between language and its users, focusing on how meaning is shaped by context, intention, and interaction. Within this framework, the research highlights the key pragmatic characteristics of the text, including intentionality, addressability, informativeness, modality, evaluation, and contextual dependence. Each of these features contributes to the text’s ability to convey the author’s communicative intent and to influence the addressee’s perception and interpretation. The article also discusses the role of pragmatic categories such as presupposition, implication, and deixis in ensuring coherence, relevance, and expressiveness. Through the analysis of various text types, the study demonstrates that pragmatic features are closely related to the social and situational factors of communication, reflecting the dynamic interaction between the speaker, the listener, and the discourse environment. Thus, the pragmatic approach provides a comprehensive understanding of how linguistic choices shape meaning and effectiveness in communication.